Collagen-based artificial cornea with double-layer structure and capable of being epithelialized quickly and preparation method of collagen-based artificial cornea
By adopting a collagen-based artificial corneal design with a bilayer structure, the combination of loose layer and compact layer is used to solve the problems of slow epithelialization process and poor material stability in the prior art, rapid epithelialization and long-term stability are achieved, the risk of infection is reduced, and excellent mechanical and biocompatibility is provided.
Patent Information
- Application Number
- CN202411842034.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-13
- Publication Date
- 2025-03-04
- Estimated Expiration
- 2044-12-13
AI Technical Summary
The existing biosynthetic process of artificial cornea is slow after surgery, leading to an increased risk of eye infection, and poor stability of the material in the body, affecting transparency and vision.
A collagen-based artificial corneal design adopts a bilayer structure, where the upper layer is a loose layer that is easy to degrade, promoting epithelial cell migration and proliferation; the lower layer is a compact layer with a slow degradation rate, providing thickness support and light conduction performance. The bilayer structure artificial cornea is prepared by technical steps such as electrochemical deposition, ultraviolet cross-linking and chemical cross-linking.
Rapid epithelialization is achieved, the risk of postoperative infection is reduced, and the high light transmission, excellent mechanical properties and good biocompatibility are achieved, ensuring long-term stability of the cornea and visual recovery.
Smart Images

Figure CN119548677A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of biomedical materials, and in particular to a collagen-based artificial cornea with a double-layer structure capable of rapid epithelialization and a preparation method thereof. Background Art
[0002] The cornea is crucial to the ocular function of the eye. However, as the outer barrier of the eye tissue, the cornea is susceptible to physical and chemical damage or invasion by pathogenic factors, which can cause corneal diseases and even blindness. For example, corneal opacity caused by mechanical trauma, corneal damage and lesions caused by chemical burns, and corneal scars caused by bacterial and fungal infections caused by microbial sources, etc., can cause a sharp decline in vision. Clinically, the most common treatment for severe corneal surface damage is to remove part of the patient's diseased lamellar corneal tissue and replace it with a donor cornea, which is called lamellar corneal transplantation, which is currently the gold standard for clinical surgery. In traditional lamellar corneal transplantation, the depth and diameter of the corneal tissue to be dissected are first determined according to the size of the diseased tissue, and then the diseased tissue is removed with a trephine and an ophthalmic scalpel. Finally, the donor cornea is sutured and fixed to the ocular surface with ophthalmic surgical sutures.
[0003] However, the success of the transplant operation mainly depends on two factors: one is the epithelialization rate. There is no epithelial cell layer on the surface of the donor cornea just after the transplant. The corneal limbus stem cells proliferate and migrate, causing the corneal epithelial cells to migrate from the edge of the surgical area to the surgical area, and finally cover the entire donor cornea to form a multi-layer cell layer. This process is corneal epithelialization. Corneal epithelialization is very important for postoperative recovery and is a manifestation of the recipient's acceptance of the donor. The epithelial cell layer is the first barrier of the eyeball against the external environment, and it is also crucial to the refractive ability of the eye. Rapid epithelialization can prevent external toxins and microorganisms from infecting the ocular surface. It can also protect the transplanted material from damage and degradation caused by eyelid friction or ocular surface secretions. Therefore, if epithelialization cannot be completed for a long time after surgery, it is easy to lead to surgical failure. The second is the biocompatibility and optical and mechanical properties of the donor cornea itself, such as refractive power, transparency, tensile strength, elastic modulus, etc.
[0004] Although lamellar keratoplasty can achieve good results in the treatment of corneal diseases, the shortage of allogeneic donor corneas, which are the gold standard, is still a global obstacle. Therefore, the development of artificial corneas has become an urgent need. At present, artificial corneas used for lamellar transplantation are mainly divided into two categories: decellularized biological corneas and biosynthetic artificial corneas. Decellularized biological corneas have good biocompatibility, can retain the natural extracellular matrix structure and active substances of the cornea, and achieve rapid epithelialization, but they are mainly derived from pig corneas. Such animal-derived materials will inevitably have risks such as antigen and virus residues during processing. After implantation, the cornea becomes turbid due to a large rejection reaction. The storage conditions are also relatively harsh, and personalized customization cannot be achieved. Before use, doctors need to spend a long time to trim the implant to match the patient's lesions, which prolongs the entire operation time. Biosynthetic artificial corneas have received widespread attention in recent years. Most of them are based on collagen / recombinant collagen, and then undergo subsequent performance enhancement designs. They have high biocompatibility, little stimulation to tissue cells, are degradable in the body, have low foreign body sensation, and can imitate the structure and function of the natural cornea to the greatest extent. They also have the two major advantages of synthetic polymer artificial corneas and decellularized biological corneas, and have potential application value in corneal damage repair.
[0005] At the same time, there are some problems that need to be improved in the biosynthetic artificial cornea. The most commonly used materials include collagen, silk fibroin, gelatin, chitosan, etc. These biosynthetic artificial corneas have good biocompatibility and non-toxicity. However, since the current biosynthetic cornea is usually a homogenous body, the surface hardness of the artificial cornea is high and there is no biologically active substance that promotes epithelialization. It is usually impossible to quickly complete epithelialization within 1-2 weeks after surgery. Patent CN118557801 A adds a carboxylated silk fibroin solution to a collagen solution for cross-linking, and after casting the obtained collagen-carboxylated silk fibroin composite system into a mold, it is fully dried to obtain a carboxylated silk fibroin-enhanced collagen-based corneal repair material, but the resulting corneal morphology is irregular and the rapid epithelialization process cannot be completed quickly. Patent CN114618016 A obtains a collagen-based artificial cornea consistent with the shape of the cornea on the electrode by extracting collagen, assembling collagen using electrochemical deposition technology, and chemical cross-linking steps. Although the cornea obtained by this method has a transparency of more than 80% and a controllable thickness, its epithelialization process is slow and the wound surface cannot be closed in a short time, which sharply increases the risk of eye infection and may even cause a series of malignant lesions such as corneal ulcers, thereby affecting corneal transparency and scar formation, causing irreversible damage to vision. Therefore, developing a type of biosynthetic artificial cornea that can rapidly epithelialize and ensure that the main body of the artificial cornea material is isolated from the external environment has great clinical significance for the stable existence and transparency of the biosynthetic artificial cornea in the body. Summary of the invention
[0006] The purpose of the present invention is to provide a collagen-based artificial cornea with a double-layer structure and capable of rapid epithelialization and a preparation method thereof, so as to overcome the deficiencies in the prior art.
[0007] To achieve the above object, the present invention provides the following technical solutions: The present application discloses a method for preparing a collagen-based artificial cornea with a double-layer structure and capable of rapid epithelialization, comprising the following steps: S1. Preparation of collagen solution: adding collagen to acetic acid solution and stirring to dissolve, adding plasticizer after complete dissolution, stirring evenly and centrifuging to degas, obtaining a high-concentration collagen solution and a low-concentration collagen solution; the concentration of the high-concentration collagen solution is 0.3% to 0.5% w / v, and the concentration of the low-concentration collagen solution is 0.1% to 0.25% w / v; S2. Primary electrochemical deposition: taking a high concentration collagen solution for electrochemical deposition, connecting the platinum mesh to the positive electrode, the titanium sheet to the negative electrode, and the electrode plate to a DC power supply to obtain a collagen film 1; S3. One-time UV cross-linking: After the collagen membrane is dehydrated with anhydrous ethanol, it is photo-cross-linked by irradiation with strong UV light; S4 chemical crosslinking: the collagen membrane after the UV crosslinking treatment in step S3 is immersed in a 4-(4,6-dimethoxytriazine-2-yl)-4-methylmorpholine hydrochloride solution to obtain a compact layer by chemical crosslinking; S5. Secondary electrochemical deposition: Connect the titanium sheet with the compacting layer to the negative electrode, connect the platinum mesh to the positive electrode, pour the low-concentration collagen solution into the deposition tank, immerse the compacting layer, and perform secondary electrochemical deposition to obtain a second collagen film on the compacting layer; S6. Secondary UV cross-linking: After the collagen membrane 2 is dehydrated with anhydrous ethanol, it is irradiated with weak UV light for secondary photo-cross-linking to obtain a loose layer. The loose layer is combined with the compact layer to form the double-layer structure and the collagen-based artificial cornea capable of rapid epithelialization.
[0008] Preferably, the collagen is type I collagen.
[0009] Preferably, the plasticizer is selected from any one or a combination of glycerol, polyethylene glycol, polypropylene glycol, and citrate plasticizers, and the concentration of the plasticizer is 10% to 20% v / v.
[0010] Preferably, the concentration of the acetic acid solution is 1% to 3% v / v.
[0011] Preferably, in step S2, the DC power supply selects a constant current mode of 1-4A, and the deposition time is 30-60min; in step S4, the DC power supply selects a constant current mode of 1-4A, and the deposition time is 10-30min.
[0012] Preferably, the intensity of the strong ultraviolet light in step S3 is 600-1000 μw / cm 2 , the time is 30~60min; the intensity of the weak ultraviolet light in step S6 is 10~200μw / cm 2 , time is 1~10min.
[0013] Preferably, in step S4, the concentration of the 4-(4,6-dimethoxytriazine-2-yl)-4-methylmorpholine hydrochloride solution is 0.01% to 0.04% w / w, and the immersion time is 1 to 5 hours.
[0014] Preferably, the method further comprises step S7: washing the double-layered collagen-based artificial cornea capable of rapid epithelialization prepared in step S6 with PBS and storing it in a PBS buffer containing recombinant human epidermal growth factor; the concentration of the recombinant human epidermal growth factor is 0.01%-0.03% w / v.
[0015] The present invention also discloses a collagen-based artificial cornea with a double-layer structure and capable of rapid epithelialization, which is prepared by the preparation method of a collagen-based artificial cornea with a double-layer structure and capable of rapid epithelialization as described above; it is applied to corneal diseases caused by corneal damage and corneal infection, and the double-layer artificial cornea of the present invention is transplanted to corneal disease patients through lamellar transplantation. The epithelial healing of lamellar transplantation affects the recovery of postoperative vision, and even delayed healing of the epithelium may cause problems such as graft infection, graft matrix dissolution, and ocular surface ulcers. The upper layer of the double-layer structure of the present invention is a loose layer that is easy to degrade, which is conducive to the migration of epithelial cells, and accelerates the lamellar transplantation to complete the autologous corneal epithelialization. At the same time, the degradation rate of the lower compact layer is slow, providing a certain thickness support and light penetration performance.
[0016] Beneficial effects of the present invention: 1. The invention discloses a collagen-based artificial cornea with a double-layer structure and rapid epithelialization, which has high light transmittance and mechanical properties that meet clinical requirements: the transmittance at 600nm is higher than 90%, the tensile strength is higher than 1Mpa, and the elastic modulus is higher than 10MPa. The low swelling rate can avoid the product from compressing the autologous corneal tissue, reduce the mechanical stimulation to the eye tissue, and improve the comfort after implantation.
[0017] 2. Excellent biocompatibility: The raw materials are type I collagen and a small amount of pharmaceutical grade plasticizers, which have little stimulation to tissue cells and do not produce inflammatory reactions. The artificial cornea has a double-layer structure. The upper layer is a loose layer that is easy to degrade, providing an area for epithelial cells to migrate and proliferate. At the same time, it decomposes into small molecular amino acids after degradation, providing nutrients for tissue cells, and is also conducive to the rapid completion of epithelialization in lamellar transplantation surgery, avoiding contact between the lesion area and the outside world, which may lead to infection.
[0018] 3. Long-term stability and synergistic promotion of epithelialization: The lower layer is a compact layer with a slow degradation rate. It can provide a certain thickness support for the cornea and cooperate with other structures of the cornea to achieve refractive function. At the same time, by increasing the cross-linking strength, it can exist stably for a long time. The epidermal growth factor carried on the surface of the artificial cornea can synergistically promote the rapid growth of corneal epithelial cells, complete epithelialization, ensure that the main body of the artificial cornea material is isolated from the external environment, and avoid degradation, infection, inflammation and other adverse conditions caused by the outside world to the material and surrounding tissues. The operation steps are simple and convenient for large-scale production.
[0019] The features and advantages of the present invention will be described in detail through embodiments in conjunction with the accompanying drawings. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 This is the proliferation of cells in Example 2.
[0021] Figure 2 Schematic diagram of the penetration experiment.
[0022] Figure 3 This is a trend chart of in vitro enzymatic hydrolysis.
[0023] Figure 4 This is a graph simulating in vitro degradation trends using artificial tears.
[0024] Figure 5 Schematic diagram of the collagen-based double-layer artificial cornea.
[0025] Figure 6 Fluorescent staining of the rabbit epithelium on the second day and one week after lamellar corneal transplantation. DETAILED DESCRIPTION
[0026] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention is further described in detail below through the accompanying drawings and embodiments. However, it should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the scope of the present invention. In addition, in the following description, the description of known structures and technologies is omitted to avoid unnecessary confusion of the concept of the present invention.
[0027] The present invention provides a method for preparing a collagen-based artificial cornea with a double-layer structure capable of rapid epithelialization, comprising the following steps: S1. Preparation of collagen solution: adding collagen to acetic acid solution and stirring to dissolve, adding plasticizer after complete dissolution, stirring evenly and centrifuging to degas, obtaining a high-concentration collagen solution and a low-concentration collagen solution; the concentration of the high-concentration collagen solution is 0.3% to 0.5% w / v, and the concentration of the low-concentration collagen solution is 0.1% to 0.25% w / v; Specifically, the collagen is type I collagen; the plasticizer is selected from any one or a combination of glycerol, polyethylene glycol, polypropylene glycol, and citrate plasticizers, and the concentration of the plasticizer is 10% to 20% v / v; the concentration of the acetic acid solution is 1% to 3% v / v S2. Primary electrochemical deposition: taking a high concentration collagen solution for electrochemical deposition, connecting the platinum mesh to the positive electrode, the titanium sheet to the negative electrode, and the electrode plate to a DC power supply to obtain a collagen film 1; Specifically, the DC power supply selected the constant current mode of 1~4A, and the deposition time was 30~60min; S3. One-time UV cross-linking: After the collagen membrane is dehydrated with anhydrous ethanol, it is photo-cross-linked by irradiation with strong UV light; Specifically, the intensity of strong ultraviolet light is 600~1000μw / cm 2 , time is 30~60min; S4 chemical crosslinking: the collagen membrane after the UV crosslinking treatment in step S3 is immersed in a 4-(4,6-dimethoxytriazine-2-yl)-4-methylmorpholine hydrochloride solution to obtain a compact layer by chemical crosslinking; Specifically, the concentration of the 4-(4,6-dimethoxytriazine-2-yl)-4-methylmorpholine hydrochloride solution is 0.01% to 0.04% w / w, and the soaking time is 1 to 5 hours; S5. Secondary electrochemical deposition: Connect the titanium sheet with the compacting layer to the negative electrode, connect the platinum mesh to the positive electrode, pour the low-concentration collagen solution into the deposition tank, immerse the compacting layer, and perform secondary electrochemical deposition to obtain a second collagen film on the compacting layer; Specifically, the DC power supply selects a constant current mode of 1-4A, and the deposition time is 10-30min.
[0028] S6. Secondary UV crosslinking: After the collagen membrane is dehydrated with anhydrous ethanol, it is irradiated with weak UV light for secondary photocrosslinking to obtain a loose layer, and the loose layer is combined with the compact layer to form the double-layer structure and the collagen-based artificial cornea capable of rapid epithelialization, such as Figure 5 .
[0029] Among them, the intensity of weak ultraviolet light is 10~200μw / cm 2 , time is 1~10min.
[0030] The method further comprises step S7: washing the double-layered collagen-based artificial cornea capable of rapid epithelialization prepared in step S6 with PBS and storing it in a PBS buffer solution containing recombinant human epidermal growth factor; the concentration of the recombinant human epidermal growth factor is 0.01%-0.03% w / v.
[0031] Example 1 In this embodiment, a method for preparing an artificial cornea with a collagen-based double-layer structure is provided, which is specifically as follows: (1) Preparation of collagen solution: Use 1% v / v acetic acid solution as solvent to prepare 0.3% w / v high-concentration collagen solution and 0.1% w / v low-concentration collagen solution. Stir and dissolve until there is no obvious lumps in the solution. After complete dissolution, add 10% v / v plasticizer and stir evenly.
[0032] (2) Bubble removal: The collagen solution was subjected to centrifugal degassing treatment at a speed of 8000 rpm for 15 min.
[0033] (3) Primary electrochemical deposition: Under a low temperature environment of 4°C, 0.3% w / v high concentration collagen solution was electrochemically deposited. The platinum mesh was connected to the positive electrode, the titanium sheet was connected to the negative electrode, and the electrode plate was connected to a DC source for electrochemical deposition. Collagen film material was obtained on the titanium sheet. The DC power supply selected the constant current mode of 1A, and the deposition time was 30 min.
[0034] (4) Primary UV cross-linking: The collagen membrane on the titanium sheet was immersed in anhydrous ethanol for dehydration and then irradiated with 600 μw / cm2 UV light for 30 min for UV cross-linking.
[0035] (5) Chemical cross-linking: The collagen membrane was soaked in 0.01% w / w DMTMM solution for 1 h to perform chemical cross-linking to obtain a compact layer.
[0036] (6) Secondary electrochemical deposition: Under low temperature environment of 8°C, the titanium sheet with compacted layer was connected to the negative electrode, and the platinum mesh was connected to the positive electrode. A 0.1% w / v low concentration collagen solution was poured into the deposition tank to immerse the compacted layer for secondary electrochemical deposition. The DC power supply selected constant current mode of 1A and the deposition time was 10 min.
[0037] (7) Secondary UV cross-linking: A new layer of collagen membrane is covered on the compacting layer, dehydrated with ethanol, and irradiated under 10 μw / cm2 UV light for 10 min for UV cross-linking.
[0038] (8) Film peeling: The titanium sheet and the collagen membrane are soaked in pure water together. When the collagen membrane is fully moistened, the collagen membrane is slowly peeled off from the titanium sheet to obtain a double-layer artificial cornea.
[0039] (9) PBS cleaning: The artificial cornea was immersed in PBS buffer and shaken for cleaning. 1L PBS solution was shaken for 10 minutes, and the cleaning was performed 5 times in total.
[0040] (10) Storage method: The prepared artificial cornea was stored in PBS buffer containing 0.01% w / v rhEGF.
[0041] Example 2 In this embodiment, a method for preparing an artificial cornea with a collagen-based double-layer structure is provided, which is specifically as follows: (1) Preparation of collagen solution: Use 2% v / v acetic acid solution as solvent to prepare 0.38% w / v high-concentration collagen solution and 0.12% w / v low-concentration collagen solution. Stir and dissolve until there is no obvious lumps in the solution. After complete dissolution, add 15% v / v plasticizer and stir evenly.
[0042] (2) Bubble removal: The collagen solution was subjected to centrifugal degassing treatment at a speed of 8000 rpm for 15 min.
[0043] (3) Primary electrochemical deposition: Under a low temperature environment of 5°C, 0.38% w / v high concentration collagen solution was electrochemically deposited. The platinum mesh was connected to the positive electrode, the titanium sheet was connected to the negative electrode, and the electrode plate was connected to a DC source for electrochemical deposition. Collagen film material was obtained on the titanium sheet. The DC power supply selected the constant current mode of 2A, and the deposition time was 40 min.
[0044] (4) Primary UV cross-linking: The collagen membrane on the titanium sheet was immersed in anhydrous ethanol for dehydration and then irradiated with 800 μw / cm2 UV light for 40 min.
[0045] (5) DMTMM cross-linking: The collagen membrane was soaked in 0.02% w / w DMTMM solution for 4 h to perform chemical cross-linking to obtain a compact layer.
[0046] (6) Secondary electrochemical deposition: At a low temperature of 4°C, the titanium sheet with a compacted layer was connected to the negative electrode, the platinum mesh was connected to the positive electrode, and a 0.12% w / v low-concentration collagen solution was poured into the deposition tank to immerse the compacted layer for secondary electrochemical deposition. The DC power supply selected the constant current mode of 2A and the deposition time was 15 min.
[0047] (7) Secondary UV cross-linking: A new layer of collagen membrane is covered on the compacting layer, dehydrated with ethanol, and irradiated under 100 μw / cm2 UV light for 2.5 min for UV cross-linking.
[0048] (8) Film peeling: The titanium sheet and the collagen membrane are soaked in pure water together. When the collagen membrane is fully moistened, the collagen membrane is slowly peeled off from the titanium sheet to obtain a double-layer artificial cornea.
[0049] (9) PBS cleaning: The artificial cornea was immersed in PBS buffer and shaken for cleaning. 3L PBS solution was shaken for 30 minutes, and washed 8 times in total.
[0050] (10) Storage method: The prepared artificial cornea was stored in PBS buffer containing 0.018% w / v rhEGF.
[0051] Example 3 In this embodiment, a method for preparing an artificial cornea with a collagen-based double-layer structure is provided, which is specifically as follows: (1) Preparation of collagen solution: Use 3% v / v acetic acid solution as solvent to prepare 0.5% w / v high-concentration collagen solution and 0.25% w / v low-concentration collagen solution. Stir and dissolve until there is no obvious lumps in the solution. After complete dissolution, add 20% v / v plasticizer and stir evenly.
[0052] (2) Bubble removal: The collagen solution was subjected to centrifugal degassing treatment at a speed of 8000 rpm for 15 min.
[0053] (3) Primary electrochemical deposition: Under a low temperature environment of 8°C, 0.5% w / v high concentration collagen solution was electrochemically deposited. The platinum mesh was connected to the positive electrode, the titanium sheet was connected to the negative electrode, and the electrode plate was connected to a DC source for electrochemical deposition. Collagen film material was obtained on the titanium sheet. The DC power supply selected the constant current mode of 4A, and the deposition time was 60 min.
[0054] (4) Primary UV cross-linking: The collagen membrane on the titanium sheet was immersed in anhydrous ethanol for dehydration and then irradiated with 1000 μw / cm2 UV light for 60 min.
[0055] (5) DMTMM cross-linking: The collagen membrane was soaked in 0.04% w / w DMTMM solution for 5 h to perform chemical cross-linking to obtain a compact layer.
[0056] (6) Secondary electrochemical deposition: Under low temperature of 5°C, the titanium sheet with compacted layer was connected to the negative electrode, the platinum mesh was connected to the positive electrode, and a 0.25% w / v low concentration collagen solution was poured into the deposition tank to immerse the compacted layer for secondary electrochemical deposition. The DC power supply selected the constant current mode of 4A and the deposition time was 30 min.
[0057] (7) Secondary UV cross-linking: A new layer of collagen membrane is covered on the compacting layer, dehydrated with ethanol, and irradiated under 200 μw / cm2 UV light for 1 min to perform UV cross-linking.
[0058] (8) Film peeling: The titanium sheet and the collagen membrane are soaked in pure water together. When the collagen membrane is fully moistened, the collagen membrane is slowly peeled off from the titanium sheet to obtain a double-layer artificial cornea.
[0059] (9) PBS cleaning: The artificial cornea was immersed in PBS buffer and shaken for cleaning. 4L PBS solution was shaken for 60 minutes, and washed 10 times in total.
[0060] (10) Storage method: The prepared artificial cornea was stored in PBS buffer containing 0.03% w / v rhEGF.
[0061] Comparative Example 1 The only difference between this comparative example and Example 2 is that no plasticizer is added to the collagen solution.
[0062] Comparative Example 2 The only difference between this comparative example and Example 2 is that no ultraviolet light is used to photo-crosslink the artificial cornea.
[0063] Comparative Example 3 The only difference between this comparative example and Example 2 is that DMTMM is not used to chemically cross-link the artificial cornea.
[0064] Comparative Example 4 The only difference between this comparative example and Example 2 is that no secondary electrochemical deposition is performed.
[0065] Experiment 1 The light transmittance, water content, mechanical properties, swelling rate and ion permeability of the artificial cornea obtained in the above examples and comparative examples were tested. Five parallel samples were tested in each group and the average value was taken. The specific test method is as follows: 1. Transmittance: Take a sample, wipe off the surface moisture with absorbent paper, place the sample in the center of the transmittance meter, and select the 600nm band for measurement.
[0066] 2. Moisture content: Take a sample and determine it according to the second method, drying method, in Part IV 0832 Moisture Determination Method of the Pharmacopoeia (2020 Edition).
[0067] 3. Mechanical properties: Take the samples after special sample preparation, measure their width and thickness, and test them at room temperature at a tensile rate of 50mm / min.
[0068] 4. Swelling rate: Weigh the sample and record the mass. Then place the sample in a swelling tube, add 20 mL of solvent into the tube, cover the tube tightly and place it in a constant temperature bath at 25℃±0.1℃. Weigh the mass of the swollen body once every 3 hours using the same method until the difference between the two weighing results of the swollen body does not exceed 0.019, which means that the swelling equilibrium has been reached.
[0069] 5. Osmotic performance: The sample is fixed between the osmotic chamber (containing nutrient solution) and the receptor chamber (containing deionized water), and then the solutions in the two chambers are uniformly stirred with an electromagnetic stirrer. The concentration of the nutrient solution (tryptophan solution) in the receptor chamber is then tested. The principle of calculating the permeability coefficient is as follows Figure 2 Shown: Where P is the permeability coefficient; V and S represent the volume of the solution in the chamber and the membrane area between the chambers, respectively; d represents the thickness of the wet sample; t is the diffusion time; C0 is the initial ion concentration in the permeation chamber, and C is the ion concentration in the receptor chamber at the target time (1, 6, 12, 18, and 24 h of immersion, respectively).
[0070] 6. In vitro enzymatic hydrolysis performance: Under the clean bench, measure 5mL of Tris-HCl solution and fill it into a 15mL centrifuge tube. Use tweezers to clamp the artificial cornea, put it into a sterile centrifuge tube containing 5mL of Tris-HCl solution, seal it, and place it in a 37℃ water bath for 1 hour. After the end, take out the artificial cornea clamp, gently wipe off the surface moisture, and weigh it as the original weight. Then add the mother liquor activated in a 37℃ water bath for 1 hour to the above centrifuge tube, with 88.3μL of mother liquor in each tube, shake well, seal it, and place it at 37℃ for in vitro enzymatic hydrolysis experimental observation. Change the enzyme solution every 8 hours (need to be activated for 1h before use) to maintain enzyme activity. Observe and record the status and residual weight of the sample until the sample is completely enzymatically hydrolyzed and the degradation trend is as shown in the attached Figure 3 shown.
[0071] 7. Artificial tears simulated in vitro degradation: Weigh the artificial cornea as the original weight. Under the clean bench, measure 5 mL of artificial tears and put it into a 15 mL centrifuge tube. Use tweezers to grab the artificial cornea, put it into the above sterile centrifuge tube, seal it, and place it in a 37°C constant temperature shaker to observe and record the state of the sample and the remaining weight until the sample is completely degraded. The degradation trend is as shown in the attached figure. Figure 4 shown.
[0072] The above test results are shown in Table 1 below.
[0073] Table 1 The results show that the artificial cornea prepared by the method of the present invention has a transmittance of more than 90% at 600nm, excellent optical properties, avoiding the occurrence of light blocking caused by the sample itself, a water content of more than 85%, and the transmittance and water content are similar to those of a healthy human cornea, a tensile strength of more than 1.5MPa, an elastic modulus of more than 10MPa, and excellent mechanical properties; the swelling rates of the artificial corneas in Examples 1-3 are all lower than 15%, which can avoid nerve compression of the product on the autologous cornea, reduce mechanical stimulation to the eye tissue, and improve comfort after implantation; at the same time, the tryptophan permeability coefficient is similar to that of a healthy human cornea, proving that the product can support the transmission of small molecule nutrients, ensure the absorption of nutrients in the surrounding tissues after surgery, and promote wound repair; in terms of the simulated degradation time of artificial tears in vitro, the cycle is about 80-100 days. As time goes by, the upper layer of the artificial cornea begins to degrade after one week, while the lower layer remains intact. The in vitro enzymatic hydrolysis time of the examples is more than 90h, and the enzymatic resistance of the comparative examples is significantly weakened, indicating that the cross-linking method of this product has a significant effect on improving the anti-enzymatic performance. The upper layer of the double-layer structure is a loose layer, which degrades faster than the compact layer under two simulated degradation conditions, which is conducive to the migration and proliferation of epithelial cells. The collagen of the loose layer is degraded into small molecule amino acids, which provide the cells with the nutrients they need, promote epithelialization, ensure the rapid sealing and closure of the corneal tissue, and prevent external bacteria from entering the corneal tissue to cause subsequent infection. The lower layer is a compact layer, which has a slower degradation rate. As a guide for tissue regeneration, it can provide a certain thickness support and light conduction performance for the cornea.
[0074] Experiment 2 Cytotoxicity test: Under sterile operation, the corneas prepared in Example 2 were taken and the 2 15.00 mL of extraction medium (MEM with 10% fetal bovine serum (1xMEM)) was added at a ratio of 10% / mL. After extraction at 37°C for 24 h, the extraction stock solution was obtained. The extraction stock solution was filtered with a 0.22 μm sterile filter membrane before use. The cell suspension with a density of 1×104 cells / mL was inoculated into each group of parallel wells. 100 mL of cell suspension was inoculated into each well and the mixture was incubated at 37°C with 5% CO 2 The cells were cultured in an incubator for 24 hours. After the culture was completed, the original culture medium was discarded and the sample extract was added. Each well was inoculated with 100 mL. The culture was then continued for 72 hours. After the culture was completed, the morphology of the cultured cells was observed under a microscope. The results are shown in the attached figure. Figure 1 .
[0075] It can be seen from the results that the artificial cornea prepared by the method of the present invention has good cell affinity and biocompatibility, has little stimulation to cells, and can ensure the normal growth of cells.
[0076] Experiment 3 Observation of epithelialization in rabbit corneal lamellar transplantation surgery: New Zealand rabbits weighing 2.5-3 kg were selected for in vivo animal experiments. After general anesthesia, oxybuprocaine hydrochloride eye drops were used for local anesthesia, and the surgery was performed under a sterile environment. A 4.5 mm trephine drill was used to drill a 150-200 μm deep implant bed in the center of the rabbit cornea. During the operation, the cornea in Example 2 and the cornea in Comparative Example 4 were taken out of the preservation solution and sutured with 10-0 surgical sutures, respectively. On the second day and first week after the operation, fluorescein sodium ophthalmic test paper was moistened at the implantation site to perform fluorescent staining on the defective area, and cobalt blue slit lamp fluorescent staining photography was used to observe the corneal epithelialization. Figure 6 .
[0077] The experimental results show that the double-layer artificial cornea prepared by the method of the present invention has a faster epithelial rate. On the one hand, it was found in clinical trials that the release of rhEGF has a very significant promoting effect on the healing of corneal epithelial damage. On the other hand, because the upper layer of the implant is thin and loose, this material is more conducive to cell adhesion and can promote the migration of epithelial cells, thereby promoting the repair process of epithelialization. Other biosynthetic artificial corneas have only one compact surface structure in structural design, and their smooth surface is not conducive to cell climbing, and the epithelial rate is relatively slow, which ultimately leads to clinical effects that do not meet expectations. The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modification, equivalent substitution or improvement made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a collagen-based artificial cornea with a double-layer structure and capable of rapid epithelialization, characterized in that: The steps include: S1. Preparation of collagen solution: adding collagen to acetic acid solution and stirring to dissolve, adding plasticizer after complete dissolution, stirring evenly and centrifuging to degas, obtaining a high-concentration collagen solution and a low-concentration collagen solution; the concentration of the high-concentration collagen solution is 0.3% to 0.5% w / v, and the concentration of the low-concentration collagen solution is 0.1% to 0.25% w / v; S2. Primary electrochemical deposition: taking a high concentration collagen solution for electrochemical deposition, connecting the platinum mesh to the positive electrode, the titanium sheet to the negative electrode, and the electrode plate to a DC power supply to obtain a collagen film 1; S3. One-time UV cross-linking: After the collagen membrane is dehydrated with anhydrous ethanol, it is photo-cross-linked by strong UV irradiation; S4 chemical crosslinking: the collagen membrane after the UV crosslinking treatment in step S3 is immersed in a 4-(4,6-dimethoxytriazine-2-yl)-4-methylmorpholine hydrochloride solution to obtain a compact layer by chemical crosslinking; S5. Secondary electrochemical deposition: Connect the titanium sheet with the compacting layer to the negative electrode, connect the platinum mesh to the positive electrode, pour the low-concentration collagen solution into the deposition tank, immerse the compacting layer, and perform secondary electrochemical deposition to obtain a second collagen film on the compacting layer; S6. Secondary UV cross-linking: After the collagen membrane 2 is dehydrated with anhydrous ethanol, it is irradiated with weak UV light for secondary photo-cross-linking to obtain a loose layer. The loose layer is combined with the compact layer to form the double-layer structure and the collagen-based artificial cornea capable of rapid epithelialization.
2. The method for preparing a collagen-based artificial cornea with a double-layer structure and capable of rapid epithelialization as claimed in claim 1, characterized in that: The collagen is type I collagen.
3. The method for preparing a collagen-based artificial cornea with a double-layer structure and capable of rapid epithelialization as claimed in claim 1, characterized in that: The plasticizer is selected from any one or a combination of glycerol, polyethylene glycol, polypropylene glycol, and citrate plasticizers, and the concentration of the plasticizer is 10% to 20% v / v.
4. The method for preparing a collagen-based artificial cornea with a double-layer structure and capable of rapid epithelialization as claimed in claim 1, characterized in that: The concentration of the acetic acid solution is 1% to 3% v / v.
5. The method for preparing a collagen-based artificial cornea with a double-layer structure and capable of rapid epithelialization as claimed in claim 1, characterized in that: In step S2, the DC power supply selects a constant current mode of 1-4A, and the deposition time is 30-60min; in step S4, the DC power supply selects a constant current mode of 1-4A, and the deposition time is 10-30min.
6. The method for preparing a collagen-based artificial cornea with a double-layer structure and capable of rapid epithelialization as claimed in claim 1, characterized in that: The intensity of the strong ultraviolet light in step S3 is 600~1000μw / cm 2 , the time is 30~60min; the intensity of the weak ultraviolet light in step S6 is 10~200μw / cm 2 , time is 1~10min.
7. The method for preparing a collagen-based artificial cornea with a double-layer structure and capable of rapid epithelialization as claimed in claim 1, characterized in that: In step S4, the concentration of the 4-(4,6-dimethoxytriazine-2-yl)-4-methylmorpholine hydrochloride solution is 0.01% to 0.04% w / w, and the immersion time is 1 to 5 hours.
8. The method for preparing a collagen-based artificial cornea with a double-layer structure and capable of rapid epithelialization as claimed in claim 1, characterized in that: The method further comprises step S7: washing the double-layered collagen-based artificial cornea capable of rapid epithelialization prepared in step S6 with PBS and storing it in a PBS buffer solution containing recombinant human epidermal growth factor; the concentration of the recombinant human epidermal growth factor is 0.01%-0.03% w / v.
9. A collagen-based artificial cornea with a double-layer structure and capable of rapid epithelialization, characterized in that: The invention discloses a collagen-based artificial cornea having a double-layer structure and capable of rapid epithelialization, prepared by the method for preparing a collagen-based artificial cornea having a double-layer structure and capable of rapid epithelialization as described in any one of claims 1 to 8; the collagen-based artificial cornea having a double-layer structure and capable of rapid epithelialization is used for corneal diseases requiring lamellar transplantation surgery caused by corneal injury or corneal infection.
Citation Information
Patent Citations
Carboxylated silk fibroin enhanced collagen-based cornea repair material and preparation method thereof
CN118557801A
Artificial cornea and preparation method thereof
CN114618016A
Bionic cornea and preparation method thereof
CN115463258A
Combination product for corneal lesion repair and preparation method thereof
CN117138112A
Collagen molded body and method for producing the same
JP2014218453A
Cited By
Collagen membrane material capable of stably existing in body for long time and preparation method of collagen membrane material
CN121177582A